PROBABILITY AND STATISTICS SOFTWARE FOR AN ENGINEERING APPLICATION: PETROLEUM SUPPLY DEMAND MODELING - Yen, Lee Mun (Universiti Teknologi Petronas, 2006)
The impact of computer technology on organization and society is increasing as new technologies evolve and current technologies expand. Interaction and cooperation between people and machines are rapidly growing to cover more and more aspects of organizational activities. The increased use of computing facilities and the application of concepts and theories from different disciplines (like operational research, management science, artificial intelligence) have resulted in various types of computer based systems. The use of models to support decision making is common-place, particularly since the emergence of personal computer. These models have progressively been used more and more by decision makers themselves In this project, a software that incorporates a statistical model is being developed. This model will be able to assist the users in carrying out forecasting activities. The proposed models for the courseware include a multiple regression analysis and the time series models. The purpose of this software is to allow easy and painless interaction between the user and the software. The supply and demand aspects has been carefully studied to provide a better understanding of the industry. The output of the software will be used to improve engineers' and managers' decisions on topics such as whether petroleum production be increased or whether alternative energy resources development should be accelerated.